THE ORGANIZATIONAL COMMITMENT AS PERCEIVED BY THE STAFF MEMBERS OF THE FACULTY OF EDUCATION, UNIVERSITY OF KHARTOUM - Dldom, Saifaldin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
Organizational commitment is considered an essential concept for ensuring work and staff motivation in a higher education setting. Therefore, this study aimed to assess the staffsâ€™ degree of organizational commitment to the Faculty of Education, University of Khartoum. To investigate research questions, a survey questionnaire was conducted. Among 239 respondents, 106 staff members were surveyed (44.00%). The results indicated that the degree of staff affective, continuance, and normative commitment in the Faculty of Education, University of Khartoum, was high. This study also confirmed that the aggregate degree of organizational commitment among staff members in the Faculty of Education, University of Khartoum, was high. The study revealed no statistically significant difference in the degree of organizational commitment due to gender and academic rank variables. The study also found a statistically significant difference in affective and normative commitment in the degree of organizational commitment related to years of service. The study recommended improving the worldly position of the staff member to maintain a high degree of responsibility at the University of Khartoum.Â